Interventions to improve cognitive performance in chronic kidney disease: A scoping review. - Janine Farragher; Urooj K Khan; Kevin Yau; Katherine E Stewart; Tyrone G Harrison; Lisa Engel; Samantha E Seaton; Maoliosa Donald; Brenda R Hemmelgarn (PLoS ONE)
Rationale & objective Cognitive impairment is commonly associated with chronic kidney disease (CKD. A number of intervention approaches have the potential to improve cognitive performance in CKD. Our objective was to characterize interventions studied to improve cognitive performance for adults with CKD across all categories of severity, including kidney failure. Study design Scoping review following JBI methodology. Setting and study populations Adults (≥18 years) with CKD or kidney failure. Selection criteria for studies We searched 5 electronic databases for studies published up to April 5, 2024. Eligible sources were primary research studies that investigated any intervention targeting cognition in adults (≥18 years) with CKD or kidney failure. Full-text article screening was performed in duplicate. Data extraction Characteristics of interventions, populations studied, and outcomes investigated. Analytical approach Descriptive statistics and narrative syntheses. Results Seventy-one studies were included. Over half (n = 37, 52%) were conducted within the past five years, and most studies (n = 47, 66%) targeted people on maintenance hemodialysis therapy. Just over one-third of studies investigated pharmacological interventions, with much of the pharmacological or medical research focusing on anemia management or dialysis adequacy. Although recent research has expanded in focus, many other purported mechanisms of cognitive dysfunction in CKD remain understudied in interventional research. Exercise training (n = 14) was the most common nonpharmacological approach studied, but few studies have explored other promising nonpharmacological approaches such as cognitive rehabilitation interventions. Limitations Abstract screening not performed in duplicate; non-English studies excluded. Conclusion Research into cognitive interventions for people with kidney disease has primarily focused on the hemodialysis population and investigated erythropoietin stimulating agents, frequent or prolonged dialysis, and exercise, although there has been recent growth of research activity into other interventions. Future research should aim to address a broader range of purported pathophysiological mechanisms of cognitive impairment in CKD, investigate interventions for predialysis and peritoneal dialysis patients, and explore the impacts of established cognitive rehabilitation approaches.